Telling people to "rely on their reasoning" increases intentions to wear a face covering to slow down COVID‐19 transmission. Issue 3 (3rd February 2021) - Capraro, Valerio; Barcelo, Hélène
Abstract: Finding messaging to promote the use of face masks is fundamental during a pandemic. Study 1 ( N = 399) shows that telling people to "rely on their reasoning" increases intentions to wear a face mask, compared with telling them to "rely on their emotions." In Study 2 ( N = 591) we add a baseline. However, the results show only a non‐significant trend. Study 3 reports a well‐powered replication of Study 2 ( N = 930). In line with Study 1, this study shows that telling people to "rely on their reasoning" increases intentions to wear a face mask, compared to telling them to "rely on their emotions." Two internal meta‐analyses show that telling people to "rely on their reasoning" increases intentions to wear a face mask compared (1) to telling them to "rely on their emotions" and (2) to the baseline. These findings suggest interventions to promote intentions to wear a face mask.